Relationships and cooperative acts in argentinian law: concepts and ramifications (Papeles, 2024)
This article has the goal to examine the cooperative act's concept and developing within the framework of Argentinian Law. Following the review of the main aspects of cooperatives as entities of the Social Economy and their private nature, stated in the Civil and Commercial Code, this article analyze the definition of the cooperative act and its legal regulation, highlighting its importance in “cooperative legal liaisons.” ”. The shifting of “common law” because of the cooperative act and the rules and principles of cooperative law is addressed. The analysis of case laws illustrates the relevance of recognizing the associative nature of the relationships between members and cooperatives. The article concludes by highlighting the need to understand the cooperative act as an essential element in the legal interpretation of cooperative relationships.
Keywords: Cooperative act; Legal act; Co-operative societies; Social Economy; Cooperative law